Improving live weight gain in Ongole crossbred bulls through processing of Gliricidia sepium leaf meal and cassava in a supplement concentrate - Winarti, E.; Gunawan, Gunawan; Sofyan, Akhmad; Wirasti, C.A.; Noviandi, Cuk Tri; Panjono, Panjono; Agus, Ali; Harper, K.J.; Poppi, D.P. (Elsevier, 2022)
Formulating rations using locally produced protein and energy sources is an important strategy to increase beef production in developing countries. Gliricidia sepium leaf meal (GLM), dry cassava powder (DCP), soybean hulls (SBH), peanut husks (PH) and palm kernel cake (PKC) in various combinations, were processed either as a mash or a pellet, to produce a concentrate supplement diet (CSD) for Ongole crossbred bulls in an Indonesian village fattening system. Bulls were given the current feeding system (CFS) ad libitum (T0, control) and CFS ad libitum + 1 % live weight (on approximate DM basis) of five different CSD (T1, T2, T3, T4 and T5). Treatments were: T1 (CFS + CSD mash: 25 % GLM + 25 % SBH + 50 % DCP), T2 (CFS + CSD pellet: 25 % GLM + 25 % SBH + 50 % DCP), T3 (CFS + CSD pellet: 50 % GLM + 25 % SBH + 25 % DCP), T4 (CFS + CSD pellet: 50 % GLM + 5 % SBH + 20 % DCP + 10 % PH + 15 % PKC) and T5 (CFS + CSD mash: 50 % GLM + 5 % SBH + 20 % DCP + 10 % PH + 15 % PKC). The experiment was carried out for 12 weeks and arranged in a randomized complete block design with 10 head per treatment. Animals were ranked and blocked based on pre-experiment live weight. The measured experimental variables consisted of growth performance and blood profile. Results showed that CSD supplementation significantly (P < 0.05) increased dry matter intake and average daily gain of Ongole crossbred bulls without affecting the feed to gain ratio. There were no differences in the average daily gain (ADG) between CSD treatments despite a difference in crude protein (CP) content (9 vs 13 % CP) between high and low DCP inclusion levels (25 % vs 50 %) and inverse GLM inclusion, or mash vs pelleted processing method. This suggested that the response was due primarily to increased metabolisable energy supply rather than CP supply. Daily income over feed cost (IOFC) was highest in T5 treatment (38 % higher than the control) which was formulated to provide the lowest cost of CSD ration. In conclusion, pelleting did not affect the performance of bulls, GLM and DCP could be used effectively at high levels, and a least cost ration approach was most effective in increasing the daily IOFC for smallholder farmers.